Distribution of newly synthesized DT-diaphorase in rat liver. Issue 11 (November 1982) - Edlund, C.; Elhammer, Å.; Dallner, G.
Abstract : The distribution, synthesis transport, and glycosylation of rat-liver DT-diaphorase has been investigated. The enzyme could be isolated using specific antibodies, mainly from the soluble supernatant but also from microsomal vesicles, Golgi membrane, and mitochondria. 40% of the microsomal enzyme was located in the lumen or on the interior side of the membrane, the rest remaining as an integral non-extractable part of the membrane. Synthesis of DT-diaphorase takes place on both free and bound ribosomes, although it was found to be transported in a sequential manner from the rough to the smooth endoplasmic reticulum and also subsequently to the mitochondria. The rough and smooth microsomal DT-diaphorase contains covalently bound carbohydrate, but no sugar moiety could be detected bound to the cytoplasmic form of the enzyme.